Pengaruh Model Pembelajaran Read Answer Discuss Explain Create (RADEC) Berbantuan Kartu Kata pada Materi Pantun Terhadap Keterampilan Menulis Pantun Bahasa Rejang dan Literasi Budaya Siswa Kelas V Sekolah Dasar - Dahlia, Intan; Gumono; Juarsa, Osa (UNIB Press, 2025)
This research aims to determine the effect of implementing the RADEC learning model on rhyme writing skills and cultural literacy abilities of fifth grade elementary school students. This type of research is quantitative, the research method used is quasi-experimental with a non-equivalent control group design for two groups, namely the experimental group and the control group. The research samples obtained were SD Negeri 04 and 09 Tebat Karai. The research instrument used was a written test in the form of a fill-in test. The data from this research uses inferential data, namely the t-test and correlation test. The results of the research show that the results of the t-test with tcount on rhyme writing skills are 8.87, on cultural literacy skills it is 4.55, the tcount value obtained is more than ttable, so it is concluded that there is an influence of using the RADEC learning model on rhyme writing skills in the Rejang language and cultural literacy s. And the r-calculated value of Rejang language rhyme writing skills with cultural literacy is 0.5 with a significance level of α=5% r table of 0.361. Because rcount > rtable, it can be concluded that there is a relationship between Rejang language rhyme writing skills and the cultural literacy of fifth grade elementary school students.